Fluoxetine normalizes disrupted light-induced entrainment, fragmented ultradian rhythms and altered hippocampal clock gene expression in an animal model of high trait anxiety- and depression-related behavior. (8th January 2016) - Schaufler, Jörg; Ronovsky, Marianne; Savalli, Giorgia; Cabatic, Maureen; Sartori, Simone B.; Singewald, Nicolas; Pollak, Daniela D.
ABSTRACT: Introduction Disturbances of circadian rhythms are a key symptom of mood and anxiety disorders. Selective serotonin reuptake inhibitors (SSRIs) - commonly used antidepressant drugs – also modulate aspects of circadian rhythmicity. However, their potential to restore circadian disturbances in depression remains to be investigated. Materials and methods The effects of the SSRI fluoxetine on genetically based, depression-related circadian disruptions at the behavioral and molecular level were examined using mice selectively bred for high anxiety-related and co-segregating depression-like behavior (HAB) and normal anxiety/depression behavior mice (NAB). Results The length of the circadian period was increased in fluoxetine-treated HAB as compared to NAB mice while the number of activity bouts and light-induced entrainment were comparable. No difference in hippocampal Cry2 expression, previously reported to be dysbalanced in untreated HAB mice, was observed, while Per2 and Per3 mRNA levels were higher in HAB mice under fluoxetine treatment. Discussion The present findings provide evidence that fluoxetine treatment normalizes disrupted circadian locomotor activity and clock gene expression in a genetic mouse model of high trait anxiety and depression. An interaction between the molecular mechanisms mediating the antidepressant response to fluoxetine and the endogenous regulation of circadian rhythms in genetically based mood and anxiety disorders is proposed.